2017
DOI: 10.1038/s41467-017-00344-7
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies nutrient extraction and toxin delivery between bacteria

Abstract: Bacteria have developed various mechanisms by which they sense, interact, and kill other bacteria, in an attempt to outcompete one another and survive. Here we show that Bacillus subtilis can kill and prey on Bacillus megaterium. We find that Bacillus subtilis rapidly inhibits Bacillus megaterium growth by delivering the tRNase toxin WapA. Furthermore, utilizing the methionine analogue L-azidohomoalanine as a nutrient reporter, we provide evidence of nutrient extraction from Bacillus megaterium by Bacillus sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…We have previously shown that Bs kills Bm cells grown in proximity by delivering the tRNase toxin WapA via nanotubes 6 . We thus examined the ability of Bs to inhibit Bm growth, as a readout for establishment of interspecies nanotubes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that Bs kills Bm cells grown in proximity by delivering the tRNase toxin WapA via nanotubes 6 . We thus examined the ability of Bs to inhibit Bm growth, as a readout for establishment of interspecies nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria produce various apparatuses to conduct intercellular molecular exchange, including transfer of DNA, toxin delivery, as well as nutrient acquisition 6,9,32,33 . However, it remains mysterious how an organelle that physically bridges two adjacent cells is being established to execute these functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells growing within a biofilm are in continuous contact with each other, as well as with their environment and other organisms living in the same ecological niche. Bacterial interactions are thus defined by a combination of different factors including the activation of different metabolic pathways in conjunction with the production and secretion of signaling compounds, siderophores, antibiotics and quorum sensing molecules 21, 22, 23, 24, 25, 26 . These compounds can be excreted outside the cells via bacterial secretion systems, efflux pumps, transporters and membrane vesicles.…”
Section: Introductionmentioning
confidence: 99%